(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The abundance of cellulose on earth, the need for its biodegradation and the various applications of cellulolytic enzymes in commercial settings have necessitated unrestrained research for novel cellulase producing indigenous microorganisms for local production of the enzyme to meet the ever-growing and enormous demand for it. Soil sample was collected from a cassava processing mill while freshly harvested cassava was peeled and steeped in water for five days. Cellulase degrading bacteria and fungi were isolated from the cassava mill soil and the liquid waste (Cassava steeped water) on nutrient agar and potato dextrose agar using pour plate method under standard laboratory conditions for 48 hours. The isolated bacteria and fungi were identified using cellular morphology and biochemical characteristics; they were screened for cellulolytic ability on carboxyl methyl cellulose media supplemented with 0.5% Congo red and incubated for 48 hours. The bacteria isolated were Escherichial coli, Pseudomonas and Bacillus species while the fungi isolates were Aspergillus fumigatus, flavus, terreus, niger, Rhizopus species and Trichodermal species. The isolated Pseudomonas species has the highest cellulolytic ability of (18.00 mm) in terms of diameter of zone of clearance on the Congo red media among the bacteria, then the Bacillus species (15.00 mm) while the least of 1.00 mm was in the E. coli isolated. Aspergillus terreus, fumigatus and niger were the isolates with highest cellulolytic ability with zones of clearance measuring 15.00, 13.00 and 13.00 mm respectively. Conclusively, the isolated Pseudomonas, Bacillus and Aspergillus species are promising organisms as potential enzyme cellulase producer.